Thermoacoustic instability of a laminar premixed flame in Rijke tube with a hydrodynamic region - Zhao, Dan (2013)
In this work, a Rijke tube with a hydrodynamic region confined is considered to investigate its non-normality and the effect of the hydrodynamic region on the system stability behaviors. Experiments are first conducted on Rijke tubes with different lengths. It is found that the fundamental mode frequency is decreased and then increased, as the flame is placed at different axial positions at the bottom half of the tube. This trend agrees well with the prediction from the thermoacoustic model developed, of which the hydrodynamic region is modelled as an oscillating ‘airplug’ and the flame dynamics is captured by using classical G-equation. In addition, the flame as measured is found to respond differently to oncoming acoustic disturbances. Modal and non-modal stability analyses are then conducted to determine the eigenmode growth rate and the transient one of acoustic disturbances. The ‘safest’ and most ‘dangerous’ flame locations as defined as those corresponding to extreme eigenmode and transient growth rate are estimated, and compared with those from the model without the hydrodynamic region. In order to mitigate such detrimental oscillations, identification and mitigation algorithms are experimentally implemented on the Rijke tube. The sound pressure level is reduced by approximately 50 dB. To gain insights on the thermoacoustic system, transfer function of the actuated Rijke tube system is measured by injecting a broad-band white noise. Compared with the estimation from our model, good agreement is observed. Finally, the marginal stability regions are estimated.